Integrating Character Values, Religious Moderation, and Local Wisdom in Islamic Religious Education: A Conceptual Analysis - M. Albab Mananna; Salwa Aurumia Firanti; Meleza Andora; Abu Mansur; Baldi Anggara (Postgraduate Program of the State Islamic Institute of Palopo, 2026)
This study aims to analyze the integration of character values, religious moderation, and local wisdom in Islamic Religious Education (IRE) learning. This research employs a qualitative approach using library research, focusing on the analysis of relevant literature related to character education, religious moderation, and local wisdom. Data were collected from scientific journal articles, academic books, and supporting documents, and analyzed using qualitative content analysis to identify key themes and patterns. The findings reveal that character values, religious moderation, and local wisdom are interconnected elements that play a significant role in strengthening Islamic Religious Education. Character values function as the moral foundation in shaping students’ behavior, while religious moderation promotes balanced, inclusive, and tolerant attitudes. Meanwhile, local wisdom provides contextual relevance that connects learning materials with students’ social and cultural environments. The integration of these three aspects contributes to the development of students’ moral character, social awareness, and ability to live harmoniously in a multicultural society. This study concludes that an integrative approach combining moral, religious, and cultural dimensions is essential to enhance the relevance and effectiveness of Islamic Religious Education in addressing contemporary challenges. However, this study is limited to a conceptual analysis based on secondary data. Therefore, future research is recommended to examine the practical implementation of this integrative model through empirical studies.